2017 Keystone Symposia at the Fairmont Banff Springs: Exploring new concepts in innate immunity and interferon signaling at the haunted castle. (June 2017) - Gunderstofte, Camilla; Holm, Christian K.; Olagnier, David
Abstract: At the 2017 Keystone Symposia meeting, new research was presented in the fields of innate immunity and type I interferon regulation. Gathering experts from these research communities offered a unique opportunity to discuss new concepts and formulate novel approaches to modulate pathological mechanisms in human inflammatory diseases.